“See you in the next life”—playing with time in sci-fi movies: Source Code, Edge of Tomorrow, Tenet. - CURUŢIU, Horaţiu; INDOLEAN, Ion (Ekphrasis (2067-631X), 2024)
In the logic of computer-generated worlds, this article proposes a look at films in which the protagonists try to overcome a tribulation or challenge by systematically returning to the past, moving not only in space but also in time. This can be seen as unreliable narration, as the viewer cannot predict what will happen next, since the scripts of these films work in a logic of their own, defying the dynamics of a classic narrative. Source Code (Duncan Jones, 2011), Edge of Tomorrow (Doug Liman, 2014), and Tenet (Christopher Nolan, 2020) present stories that rely on this medium’s ability to play with space and time for their very appeal, being similar in many ways to video games. To better understand all mental processes spectators undergo while watching this kind of stories, we look at how they use narrative conventions to create the feeling of a video game where space and time can be collapsed into one, and where boundaries are pushed for greater freedom. At the same time, within just a decade (2010s), we can identify an important evolution of this type of cinema, which automatically entails a development of the degree of narrative complexity and of its own rules that audiences are able to grasp. Source Code repeats a short period—8 minutes; Edge of Tomorrow spans several hours—about a day; and Tenet wanders through several days, back and forth, denying the protagonist a chance to repeat an event if he is killed, but giving him the opportunity to return in the midst of defining moments for the success of his mission.